1997
DOI: 10.1128/mcb.17.11.6526
|View full text |Cite
|
Sign up to set email alerts
|

c-Rel Arrests the Proliferation of HeLa Cells and Affects Critical Regulators of the G1/S-Phase Transition

Abstract: A tetracycline-regulated system was used to characterize the effects of c-Rel on cell proliferation. The expression of c-Rel in HeLa cells led to growth arrest at the G 1 /S-phase transition, which correlated with its nuclear localization and the induction of endogenous IB␣ expression. These changes were accompanied by a decrease in E2F DNA binding and the accumulation of the hypophosphorylated form of Rb. In vitro kinase assays showed a reduction in Cdk2 kinase activity that correlated with elevated levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
4

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 75 publications
4
66
0
4
Order By: Relevance
“…There has been a conflicting evidence on whether NF-κB is important in the progression or the arrest of the cell cycle. Some have reported that NF-κB activation is necessary to cause cell cycle arrest (Bash et al, 1997). However the body of evidence in recent studies have shown that NF-κB activation is related to cell cycle progression rather than arrest in various cell types (Baldwin et al, 1991;Cressman et al, 1994;Yamada et al, 1997), and that NF-κB inhibition results in cell cycle arrest (Kaltschmidt et al, 1999;Otsuka et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a conflicting evidence on whether NF-κB is important in the progression or the arrest of the cell cycle. Some have reported that NF-κB activation is necessary to cause cell cycle arrest (Bash et al, 1997). However the body of evidence in recent studies have shown that NF-κB activation is related to cell cycle progression rather than arrest in various cell types (Baldwin et al, 1991;Cressman et al, 1994;Yamada et al, 1997), and that NF-κB inhibition results in cell cycle arrest (Kaltschmidt et al, 1999;Otsuka et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Using an inducible expression system, we found that BCL6fg almost completely suppresses cell growth and triggers both cell-cycle distortion and apoptosis. The mechanisms of BCL6fg-induced apoptosis remain to be examined, especially whether there could be a causal link between the impairment in cell cycle progression and apoptosis, as in the case of the c-rel protooncogene (Bash et al, 1997). The fact that UTA-L1 cells expressing BCL6fg hardly progress throughout S phase suggests that BCL6fg negatively regulates DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Different activation pathways of NF-B may cause the expression of proteins that promote apoptosis (eg Fas, c-myc, p53, I B␣) or inhibit apoptosis (eg TRAF2, IAP proteins, Bcl-2-like proteins). [154][155][156] In addition, NF-B activation variably controls the regulation of cell cycle Leukemia proteins (eg cyclin D1 and CDK2 kinase) [157][158][159] and the interaction with various cellular components (eg p300 and p53) that promote or induce apoptosis 160,161 (see Figure 3).…”
Section: Nf-b In Apoptosis Cell Proliferation and Tumor Initiationmentioning
confidence: 99%